2003
DOI: 10.1021/ma034213v
|View full text |Cite
|
Sign up to set email alerts
|

Insights into Structure and Mechanical Behavior of α and γ Crystal Forms of Nylon-6 at Low Strain by Infrared Studies

Abstract: Stress-induced frequency shifts of spun-cast nylon-6 films with α and γ crystals are studied at low strains with particular emphasis on vibrations related to hydrogen bonding and to the methylene chains. With increasing stress in the α films, there is a frequency increase of the NH stretching mode in the crystals where the NH bonds are preferentially aligned parallel to the tensile stretching direction. The CH2 stretching modes undergo a downward shift. This is correlated with the weakening of the hydrogen bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 45 publications
2
38
1
Order By: Relevance
“…The addition of the different nanofillers does not change the crystalline form of PA6, but the intensity of a0 0 2 reflection (at 2h = 24°) decreases relative to the a2 0 0 peak. This indicates that there is a preferential arrangement of hydrogen-bonded planes of the a crystals parallel to the surface of pure PA6 film [35,36]. Similar XRD spectra were also obtained for other nanofiller-modified samples.…”
Section: Resultssupporting
confidence: 75%
“…The addition of the different nanofillers does not change the crystalline form of PA6, but the intensity of a0 0 2 reflection (at 2h = 24°) decreases relative to the a2 0 0 peak. This indicates that there is a preferential arrangement of hydrogen-bonded planes of the a crystals parallel to the surface of pure PA6 film [35,36]. Similar XRD spectra were also obtained for other nanofiller-modified samples.…”
Section: Resultssupporting
confidence: 75%
“…In our previous work with spun cast nylon 6 film of similar molecular weight containing primarily a crystals, the A x to A z ratio for the NH stretching band was 2.34 [14], also indicating preferential arrangement of the NH bonds along the plane of the film. For the nanocomposite in this work, the A x to A z ; ratio has dropped to 1.65, showing that the arrangement of the NH bonds in the nanocomposite was more random compared to the homopolymer, even though the processing history is similar.…”
Section: Orientation Of Nylon 6 In Nanocompositementioning
confidence: 76%
“…A sample with isotropic arrangement of a crystals should show reflections of about equal intensity from both the (002) and (200) planes which give a peak at 208 [13]. Since the reflection from the (200) planes were suppressed in the spun-cast film, this indicates that there is a preferential arrangement of hydrogen-bonded planes of the a crystals parallel to the surface of the film [14].…”
Section: Orientation Of Nylon 6 In Nanocompositementioning
confidence: 99%
“…However, there are a few exceptions, where the shift is positive with tensile stress, and the difference has theoretically been attributed to stretching of the harmonic versus the anharmonic potential energy functions for C-C stretching component [15]. More recently, the FTIR technique was used to probe molecular behavior due to low strain imposed on spun cast Nylon-6 films [19]. It was found that the NH bonds underwent an upward frequency shift, while simultaneously the CH 2 stretching bonds exhibited a downward shift.…”
Section: Introductionmentioning
confidence: 99%